PENGARUH LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN SUBSEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESISA - Xena Saban, Hiezkia; Nurlia, Nurlia; Matyani, Matyani; Juwari (Fakultas Ekonomi Universitas Balikpapan, 2026)
This study aims to analyze the effect of liquidity, solvency, and profitability on firm value in Food and Beverage subsector companies listed on the Indonesia Stock Exchange. The independent variables used in this study consist of liquidity proxied by the Current Ratio (CR), solvency proxied by the Debt to Equity Ratio (DER), and profitability proxied by Return on Assets (ROA). Meanwhile, the dependent variable is firm value proxied by Price to Book Value (PBV). This research employed a quantitative research method using a purposive sampling technique. The population of this study consisted of 45 Food and Beverage subsector companies, while the sample included 23 companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The data analysis techniques applied in this research included classical assumption tests, namely the normality test, autocorrelation test, multicollinearity test, and heteroscedasticity test, as well as multiple linear regression analysis. Hypothesis testing was conducted through the correlation coefficient test (R), coefficient of determination test (R²), simultaneous test (F-test), and partial test (t-test). The results of this study indicate that profitability proxied by Return on Assets (ROA) has a positive and significant effect on firm value (PBV). On the other hand, liquidity proxied by Current Ratio (CR) and solvency proxied by Debt to Equity Ratio (DER) do not have a significant effect on firm value in Food and Beverage subsector companies listed on the Indonesia Stock Exchange